2019
DOI: 10.1074/jbc.ra118.005050
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA ANRIL regulates endothelial cell activities associated with coronary artery disease by up-regulating CLIP1, EZR, and LYVE1 genes

Abstract: Edited by Ronald C. Wek Coronary artery disease (CAD) is the leading cause of death worldwide. Long noncoding RNAs (lncRNAs) are a class of noncoding transcripts of > 200 nucleotides and are increasingly recognized as playing functional roles in physiology and disease. ANRIL is an lncRNA gene mapped to the chromosome 9p21 genetic locus for CAD identified by the first series of genomewide association studies (GWAS). However, ANRIL's role in CAD and the underlying molecular mechanism are unknown. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…This process is mediated through the expression of multiple genes regulated in both, cis and trans (69, 70). Moreover, a recent study showed that ANRIL (DQ485454) is involved in endothelial cells functions important to the development of CAD including monocyte adhesion to endothelial cells, trans-endothelial monocyte migration, and endothelial cell migration (71).…”
Section: Success Stories Of Multi-omics Studies In Cardiovascular Dismentioning
confidence: 99%
“…This process is mediated through the expression of multiple genes regulated in both, cis and trans (69, 70). Moreover, a recent study showed that ANRIL (DQ485454) is involved in endothelial cells functions important to the development of CAD including monocyte adhesion to endothelial cells, trans-endothelial monocyte migration, and endothelial cell migration (71).…”
Section: Success Stories Of Multi-omics Studies In Cardiovascular Dismentioning
confidence: 99%
“…The following genes involved in the regulation of various pathways of inflammation, according to various GWAS, are significantly associated with atherosclerotic cardiovascular diseases (CVD): CXCL12, MCP-1, TLRs, SH2B3, HLA, IL-6R, IL-5, PECAM1, and others [70]. In studies based on the proteomics approach, the crucial role of inflammation was also shown by the example of the activation of the TNF-α pathway in the vascular wall, as well as the migration of monocytes into the subendothelial compartment (ANRIL) [71,72].…”
Section: Endotype Associatedmentioning
confidence: 99%
“…Interestingly, the DQ485454 transcript was most abundant in EC lines and decreased in the coronary artery of CAD patients. Gain-and loss-of-function experiments revealed that ANRIL DQ485454 affects monocyte adhesion to ECs and transmigration across ECs along with EC migration, probably via regulation of the expression of CLIP1 , EZR , and LYVE1 [51]. Guo et al [52] have shown that human coronary artery ECs (HCAECs) viability, survival and apoptosis, and the production of proteins specific for the epithelial–mesenchymal transition along with the release of inflammatory factors and vascular-protective factors might be regulated by the ANRIL /miR-181b/NF-κB signalling pathway [52].…”
Section: Lncrnas In Atherosclerotic Plaques (Aps)mentioning
confidence: 99%